Utilization of Web-Based Geographic Information System As a Means of Tree Growth Monitoring Adoption (Case Study: Conservation Areas Hunting Park Masigit Kareumbi) - Rusdi Nengsih, Siska; Riqqi, Ahmad (Indonesian Journal of Geospatial, 2013)
Abstract. Tree Adoption Program is a program of reforestation and tree planting actively involving the community as a guardian or foster parent of the trees to be planted. The program is implemented as part of efforts to restore the ability of forests and damaged land to productive back and can ultimately increase the preservation of the environment . To help foster parents and the manager in terms of their adoption of monitoring tree , in this study a Web based GIS will be made. In this web based GIS development, Google Fusion Tables software and Google Maps is eing used. The method of WebGIS development begins with data collection in the field , then the data is entered into the database in this case is Google Fusion Tables . After that interface implementation ( interface ) based on web was built. To determine the successfully of this WebGIS, we do some test. The results from this study is a Geographic Information System ( GIS ) Web based to assist monitoring the growth and development of tree adoption and are expected to provide convenience to the foster parents and the manager in terms of monitoring. Keywords : Tree Adoption, gis web based, google fusion tables, google mapsAbstract. Tree Adoption Program is a program of reforestation and tree planting actively involving the community as a guardian or foster parent of the trees to be planted. The program is implemented as part of efforts to restore the ability of forests and damaged land to productive back and can ultimately increase the preservation of the environment . To help foster parents and the manager in terms of their adoption of monitoring tree , in this study a Web based GIS will be made. In this web based GIS development, Google Fusion Tables software and Google Maps is eing used. The method of WebGIS development begins with data collection in the field , then the data is entered into the database in this case is Google Fusion Tables . After that interface implementation ( interface ) based on web was built. To determine the successfully of this WebGIS, we do some test. The results from this study is a Geographic Information System ( GIS ) Web based to assist monitoring the growth and development of tree adoption and are expected to provide convenience to the foster parents and the manager in terms of monitoring. Keywords : Tree Adoption, gis web based, google fusion tables, google maps